2022
DOI: 10.1002/humu.24378
|View full text |Cite
|
Sign up to set email alerts
|

Short amplicon reverse transcription‐polymerase chain reaction detects aberrant splicing in genes with low expression in blood missed by ribonucleic acid sequencing analysis for clinical diagnosis

Abstract: Use of blood RNA sequencing (RNA-seq) as a splicing analysis tool for clinical interpretation of variants of uncertain significance (VUSs) found via whole-genome and exome sequencing can be difficult for genes that have low expression in the blood due to insufficient read count coverage aligned to specific genes of interest.Here, we present a short amplicon reverse transcription-polymerase chain reaction (RT-PCR) for the detection of genes with low blood expression. Short amplicon RT-PCR, is designed to span t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The increase in sensitivity of RT-PCR can be attributed to the targeted approach allowing amplification of AS events in lowly expressed genes(51), as well as amplification of AS events with low inclusion levels (in some cases accounting for NMD). For the nine cases where neither RNA-seq nor RT-PCR was able to resolve the VUS, such variants would need to be assessed with other tissue types or via alternative methods such as minigene analysis or potentially using animal models should the collection of an appropriate or adequately representative tissue not be feasible(51). The MRSD tool was used to predict the minimum required sequencing depth for genes of interest and was found to be very conservative.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in sensitivity of RT-PCR can be attributed to the targeted approach allowing amplification of AS events in lowly expressed genes(51), as well as amplification of AS events with low inclusion levels (in some cases accounting for NMD). For the nine cases where neither RNA-seq nor RT-PCR was able to resolve the VUS, such variants would need to be assessed with other tissue types or via alternative methods such as minigene analysis or potentially using animal models should the collection of an appropriate or adequately representative tissue not be feasible(51). The MRSD tool was used to predict the minimum required sequencing depth for genes of interest and was found to be very conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although SpliceAI showed that c.71-2A>C weakened the canonical acceptor site in Intron 3, we were not certain whether the third aberrant transcript resulted from c.71-2A>C. In addition, we could not completely rule out that the complex structure may be the result of spurious priming or recombination during the amplification steps. (Wai et al, 2022). reported that shortamplicon RT-PCR was a useful alternative for analyzing splicing events in genes with low median transcripts per million (TPM) in blood RNA for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have proposed the transdifferentiation of accessible tissues into specific tissue types 17 or the use of orthogonal method such as short amplicon RT-PCR to detect splice variant in lowly-expressed gene 65 , others have utilized CRISPR/Cas9 to selectively deplete unwanted overabundant sequences from existing RNA-seq libraries to increase the sensitivity of targeted genes 66 . Nonetheless, these extra manipulation steps may not be cost-effective, easily accessible, or adaptable for clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%